DESIGN OF REFUSE DERIVED FUEL (RDF) PROCESSING FACILITY FOR WASTE TREATMENT AT TEMESI FINAL DISPOSAL SITE, GIANYAR REGENCY, BALI - Alif Prakoso, Dhany
Temesi Final Disposal Site (TPA) is Gianyar District’s final disposal site. This facility should be serving 7 sub-districts in Gianyar District, Bali, which have more than 500.000 citizen. But in reality, since 1994 until 2018, it only has served and focus on the town center, the capital district of Gianyar, Gianyar City, Bali. In 2012, after TPA Temesi rehabilitation and land opening about 0.67 ha with loading capacity estimated, 79.000 m3, it’s planned to be operate until 2019, but, in fact, it’s already overloaded before 2019 which made them to transfer their waste in the landfill to the Regional Final Disposal Site Sarbagita (Denpasar-Bangli-Gianyar-Tabanan), TPA Suwung, stopping the operation of waste transferring in TPA Temesi for compacting the waste and relocate/rearrange the waste in the landfill, limiting the waste input from outsources (input from the Environmental Office or DLH only), condemnation for landfill about 0.3 ha wide on Mei 11th 2018, and until two illegal temporary disposal site (TPS) have been discovered. In fact, more than 4 ha land for the TPA is not enough to accommodate some of Gianyar District’s waste, about more than 400 m3 or more than 70 tons daily, and at the end, it’s shut again on December 20th 2018.